Characterization of porcine factor VII, X and comparison with human factor VII, X - Chen, Younan; Qiao, J.; Tan, W.; Lu, Y.; Qin, S.; Zhang, J.; Li, S.; Bu, H.; Cheng, J. (2009)
Objective: Factor VII (FVII) and factor X (FX) are two predominant molecules of coagulation cascade. Whether porcine FVII and FX could efficiently work in human circulation is important for successful pig to human liver transplantation. We compared the genetic characterizations and coagulation activities of porcine and human FVII and FX to shed insight into the further investigation of potential inter-species molecular incompatibility between porcine FVII, FX and human derived procoagulants and anticoagulants in xenotransplantation. Methods: Multiple rounds of PCR were used to screen the positive clones from a porcine liver tissue cDNA library. 5' RACE and 3' RACE were conducted to get the full-length cDNA. The three-dimensional structure of protein was modeled by Swiss-Model program. Prothrombin Time (PT) of porcine and human plasma was determined by coagulation autoanalyzer. Activities of porcine FVII and FX were detected by adding the porcine plasma into FVII or FX-deficient human plasma. Results: We cloned the full-length cDNA of porcine FVII and FX, which contained 1416 bp and 1856 bp, coding 445 and 479 amino acids, respectively. Porcine FVII and FX shared 74.08% and 73.1% amino acid identities with human FVII and FX. Sequence alignments showed that porcine FVII might have additional ?-carboxyglutamic acid in Gla domain, and one important variation of Lys62-Glu in light chain. No significant difference was observed in TF binding region of heavy chain, while 4 variations were identified in the important functional residues responsible for proteolysis activity, as Gln217-Glu, Thr151-Lys, Glu154-Val and Gln40-Leu. However, no apparent change was displayed in the 3-D model of the heavy chain of porcine FVII. When porcine FX was analyzed, great variations have been found at active peptide (Ser143 to Arg194) with only 11.6% identity. Some important variations at ?-carboxyglutamic acids and Ca2+ binding sites were identified, while high conservations were discovered at other functional sites. Comparisons on 3-D protein models demonstrated that the protein backbones of porcine and human FX were highly conserved, and little difference was shown at the molecular surface of anticoagulant binding sites S2 and S3. PT detection of porcine and human plasma showed similar results, while coagulation activities of porcine FVII and FX were remarkably higher than that of human. Conclusion: Porcine FVII and FX showed relatively high homology with human FVII and FX in nucleotide, amino acid sequences and three-dimensional structure. However, the different affinities to important macromolecules caused by genetic differences might contribute to the molecular incompatibilities in liver xenotransplantation. © 2009 Elsevier Inc. All rights reserved.